Characterization of The Optical Properties of Motor Vehicle Engine Lubricants Using the Light Polarization Method - Qidir Maulana Binu Soesanto; Ketut Sofjan Firdausi; Winarno Winarno; Wawa Gravelia Permana Prabawa (Diponegoro University Semarang Indonesia, 2022)
This paper has carried out active and non-linear optical characterizations of motor vehicle lubricants. The samples used were three two-wheeled vehicle oil with SAE labels: 10W-40, 20W-50, and 10W-30 without pre-treatment. The active optical property (natural polarization) was measured as a function of the polarizer angle without external field interference. Meanwhile, non-linear optical properties (electro-optical polarization) used changes in the polarization of light as a function of the potential difference imposed on the sample. The light sources used were a green pointer laser (532 nm) and a red pointer laser (632 nm). The results showed that the oil has active and non-linear optical properties. The natural polarization characteristic produces two polarization peaks at 30° and 60° on both wavelengths and holds to all samples. It indicates that the dimensions and shape of the molecules in all samples are identical. It is also shown by electro-optical polarization, where the change in polarization acts as a quadratic function of the potential difference with the concentric curves of the three samples, indicating identical molecules. With electro-optical polarization, the total polarization is enhanced without changing the active optical properties in the sample. It gives an advantage for developing this method as a tracer and evaluator of the molecules of other relevant materials.